Growth and yield response of different cowpea (Vigna unguiculata (L.) Walp.) varieties under varying phosphorus management - Mathew, Elizabeth; B, SUDHA; P, Shalini Pillai; John, Jacob; N, Chitra (Journal of Tropical Agriculture, 2024)
A field experiment was conducted at the Integrated Farming System Research Station (IFSRS) under Kerala Agricultural University (KAU), located at Karamana in Thiruvananthapuram, Kerala, during summer 2021 for studying the performance of grain cowpea varieties in summer rice fallows and to assess the influence of beneficial phosphorus inoculants in enhancing phosphorus availability for the crop. The treatments included three varieties of grain cowpea and five different strategies for phosphorus nutrition. The test crop varieties were Kanakamony, PGCP-6 and DC-15. Phosphorus levels comprised the KAU recommended dose of P(RDP) i.e. @30 kg P2O5 ha-1and lower doses of RDP (75 and 50 %) along with either AMF, PSB or both. Factorial RBD was the experimental design followed, with the treatment combinations laid out in three replications. Growth parameters of the crop including count of branches per plant, root mass and root volume; parameters contributing to yield including pod count per plant and average weight of pods were significantly higher for the variety PGCP-6 which also recorded higher grain yield and nutrient uptake. Application of AMF and PSB, along with 75 per cent of RDP and with 50 per cent of RDP recorded higher and comparable growth attributes (plant height, count of branches, effective nodulation, AMF root colonization, root mass and volume), yield and yield contributing attributes (harvest index, number of pods and grain yield per plant) and uptake of major plant nutrients.